Efektivitas Metode Numbered Heads Together (NHT) Untuk Meningkatkan Motivasi Belajar Pendidikan Agama Islam - Noer Kholish, Wahyu (Journal of Comprehensive Science, 2024)
The research results show the following, 1). The numbered heads together method in learning Islamic Religious Education is implemented in 3 stages, namely: a. Planning, b. Implementation, and c. Evaluation. 2). The learning motivation of students at Arif Rahman Hakim High School is identified through a number of indicators, namely. a. Foster mutual cooperation between group members and exchange ideas, b. Developing encouragement for students' enthusiasm for learning, c. Responsible for oneself and the group, d. Have good relationships with all teachers at Arif Rahman Hakim High School, South Tangerang and parents of students, e. The school environment can have a strong impact on the religious quality of students, f. The success of the Numbered Heads Together method in learning Islamic Religious Education. From the research results, it can be concluded that the Numbered Heads Together method at Arif Rahman Hakim High School plays an effective role.